PENGEMBANGAN BUKU TEKS JURNALISTIK BERBASIS PROYEK - inayatillah, fafi; Yohanes, Budinuryanta; Turistiani, Trinil Dwi (Jurnal Lentera merupakan Jurnal Prodi Pendidikan Bahasa Indonesia yang berkala mempublikasikan artikel ilmiah dari hasil penelitian berupa pengajaran dan pendidikan Bahasa Indonesia. Secara khusus, jurnal ini berisi penelitian tentang pengajaran, pen, 2019)
Abstract Project-based learning is suitable for journalistic subjects so that students are easier in mastering the concept as well as being skilled in journalistic writing. The purpose of this research is to describe process of development and quality of Project-Based Journalism textbook. This development research uses Thiangarajan model design known as four D model, that is define, design, develop, and disseminate. The instrument used in this research is the reviewer's assessment sheet and the student's assessment sheet on Project-Based Journalism Materials. The results of this research are qualified and effective Journalism Textbook. Keywords: textbook; journalism; and project.